Zdanie E jest fałszywe.
Skorzystamy z wzorów:
[tex]a^2 = a \cdot a \\\\\sqrt{\cfrac{a}{b}} = \cfrac{\sqrt{a}}{\sqrt{b}} \\\\[/tex]
Obliczamy:
[tex]a = (-2)^2 = (-2) \cdot (-2) = 4 \\\\b = \sqrt{9+16} = \sqrt{25} = 5 \\\\c = \cfrac{1}{2}(3-5)^2 = \cfrac{1}{2} \cdot (-2)^2 = \cfrac{1}{2} \cdot 4 = 2 \\\\d = \sqrt{\cfrac{25}{4}} = \cfrac{\sqrt{25}}{\sqrt{4}} = \cfrac{5}{2} = 2,5[/tex]
Należy określić, które zdanie jest fałszywe.
A. a, b, c, d > 0 → PRAWDA.
B. b > c → 5 > 2 → PRAWDA
C. c = a : 2 → 2 = 4 : 2 → PRAWDA
D. d = b : 2 → 2,5 = 5 : 2 → PRAWDA
[tex]E.\ c\not > d \rightarrow 2\not > 2,5[/tex]
Zdanie E jest fałszywe.
#SPJ2